P-002 The Financial Impact of Flow Diverters on The Endovascular Treatment of Cerebral Aneurysms. (26th July 2014) - Rai, A; Cline, B; Tarabishy, A; Patterson, J; Boo, S; Carpenter, J
Abstract : Introduction: If flow-diverters are to become the preferred mode of treating aneurysms then other than their efficacy, an analysis of their financial impact against coiling is warranted. Methodology: An IRB approved retrospective analysis was performed on 500 aneurysms treated in 427 patients. The implant-cost was calculated based on the number and type of coils that were deployed, coils that were opened but not deployed, and use of any adjunctive devices. Total aneurysm-cost included all re-treatments. The aneurysms were divided into < 6 mm, 6–11 mm and >11 mm-groups. Aneurysm-costs were compared with the hospital's cost for a flow-diverter (Pipeline TM -$12, 500). An analysis was performed to determine a cost-point based on aneurysm size, and use of adjunctive devices at which a flow-diverter became economically superior to coiling. This analysis was repeated for a hypothetically reduced price of the flow-diverter. Results: The total implant-cost per case was $11, 447(±$7523). The number of coils had a strong, positive correlation with the implant-cost (R 2 0.8, p < 0.0001). The implant-cost was $9711(±$5868) in ruptured and $12421(±$8135) in unruptured aneurysms (p < 0.0001). Aneurysm size and the use of adjunctive devices had a significant impact on implant-cost (Table 1 ). In Figure 1, the aneurysm-cost by aneurysm-size and treatment-type is shown with a superimposed cost of Pipeline TM (red line). The use of adjunctive devices did not significantly impact the implant cost in aneurysm >11 mm but was significant in the other groups. The use of flow-diverter was economically better than coils in all aneurysms >11 mm, in all aneurysms between 6–11 mm that required an adjunctive device and in all aneurysms < 6mm that required a stent. Lowering the flow-diverter cost to $10, 000 (blue-line) shows that most aneurysms above 6mm were economically viable for flow-diversion as opposed to coiling. Conclusion: The implant-cost is affected by number of coils, aneurysm-size and treatment type. A flow-diverter may be economically feasible in aneurysms >11 m, aneurysms between 6–11 mm that require an adjunctive device and aneurysms < 6 mm that require a stent. Lowering the price of a flow-diverter by $2500 magnifies this effect. As the use of flow diverters increases and more devices are available, a price adjustment will make this a very attractive first line treatment. Disclosures: A. Rai: 2; C; Stryker Neurovascular, Codman Neuro. B. Cline: None. A. Tarabishy: None. J. Patterson: None. S. Boo: None. J. Carpenter: None.